EXPLORATION OF PARENT-CHILD INTERACTION AMONG ANGANWADI CHILDREN AND THEIR PARENTS - E. AKSHAYA* (The Journal of Research ANGRAU, 2023)
The study conducted in the year 2022 aimed to analyze the parent-child interaction between Anganwadi children and their parents in the Kannur district of Kerala. Through purposive sampling, 197 samples were selected. The sample includes 114 parents from rural areas and 83 from urban areas. Data collection was done through a self made rating scale. Major findings of the study conclude that the Parent child interaction rate was more than 75%. Significant difference doesn’t exists between urban and rural areas in the Parent child interaction rate, the mean score of parent child interaction rate do not differ with age groups, educational qualification and professions. However, the mean score of Parent child interaction rate differs with income groups